A Meta-Analysis of the Effect of Subthalamic Nucleus-Deep Brain Stimulation in Parkinson's Disease-Related Pain - Diao, Yu; Bai, Yutong; Hu, Tianqi; Yin, Zixiao; Liu, Huangguang; Meng, Fangang; Yang, Anchao; Zhang, Jianguo (Frontiers in Human Neuroscience, 2021)
Pain in Parkinson’s disease (PD) is a non-motor symptom affecting quality of life and has a prevalence of 20%–80%. However, it is unclear whether subthalamic nucleus deep brain stimulation (STN-DBS), a well-established treatment for PD, is effective for PD-related pain. Thus, the objective of this meta-analysis was to investigate the efficacy of STN-DBS for PD-related pain, and explore how its duration affects the efficacy of STN-DBS. A systematic search was performed using PubMed, Embase, and the Cochrane Library. Nine studies included numerical rating scale (NRS), visual analog scale (VAS), or non-motor symptom scale (NMSS) scores at baseline and at the last follow-up visit and therefore met our inclusion criteria. These studies exhibited moderate- to high-quality evidence. Two reviewers conducted assessments for study eligibility, risk of bias, data extraction, and quality of evidence rating. Random effects meta-analysis revealed a significant change in PD-related pain as assessed by NMSS, NRS, and VAS (P < 0.01). Analysis of short and long follow-up subgroups indicated a delayed improvement in PD-related pain. These findings show: (a) the efficacy of STN-DBS for PD-related pain and provide higher-level evidence, and (b) implicate a delayed improvement in PD-related pain, which may help programming doctors with supplement selecting target and programming.